Tourism Demands for Ecotourism Spots in Indonesia Using Google Trends - MANTIKEI, BAMBANG (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The search engine is regularly used to predict future tourist visits to a destination because of the correspondence between tourist visit patterns and keyword search patterns. This means that there is an unspecified delay from someone searching for keywords until the time of his/her visit to the destination. Even so, keywords that are searched in search engines still inform interest in visiting. Therefore, this research focused on 15 ecotourism destinations in Indonesia with keyword coverage related to worldwide reach. We found that urban conservation and ecotourism destinations experienced a decrease in interest in visiting.RESUMEN El motor de búsqueda se utiliza regularmente para predecir futuras visitas turísticas a un destino debido a la correspondencia entre los patrones de esas visitas turísticas y los patrones de búsqueda de palabras clave. Esto significa que hay un retraso no especificado desde que alguien busca palabras clave hasta el momento de su visita al destino. Aun así, las palabras clave que se buscan en los motores de búsqueda todavía informan a los turistas sobre el interés de visitar. Por lo tanto, esta investigación se centró en 15 destinos de ecoturismo en Indonesia con cobertura de palabras clave relacionadas con el alcance mundial. Descubrimos que los destinos de conservación urbana y ecoturismo experimentaron una disminución en el interés de visitar.